Micro Data at the Ifo Institute for Economic Research: The Ifo Business Survey, Usage and Access - Sascha O. Becker; Klaus Wohlrabe (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2007)
The Ifo Institute for Economic Research has been conducting regular business surveyssince its foundation in 1949. The most well-known of Ifos surveys is the Ifo BusinessSurvey (ifo Konjunkturtest). The micro data of the Ifo Business Survey are accessible toexternal researchers on-site at Ifo as part of the Ifo DataPool, Ifos research data centre.This article gives an introduction of the survey questions and data coverage, an overviewof past and present research with the Ifo Business Survey, and describes the dataaccess procedure.
Keywords: C00; C80; 330; Micro data; business surveys; data access; Ifo DataPool; Ifo DataLit